THE SPILLOVER EFFECTS OF FOREIGN DIRECT INVESTMENT ON DOMESTIC ENTERPRISES IN SAVANNAKHET PROVINCE, LAOS - Binh, Hoang Xuan; Manivong, Khamkeo; Hoa, Hoang Thi (The journal of contemporary issues in business and government, 2021)
The objective of this study is to examine the spillover effects of foreign direct investment (FDI) on domestic firms in Savannakhet province, Laos. The author uses the fixed effects model (FEM) and the random effect model (REM) with the help of Eviews software and Hausman test to analyze the spillover effects of FDI on domestic firms. in Savannakhet province in the period 2013-2018. Table I-O 2018 is used to structure the relationship between domestic firms and FDI enterprises through the horizontal and vertical spillover effect of FDI on domestic firms. With the data set of sectors from 2013 to 2018, the author estimated the impact of FDI on production and business activities of FDI enterprises. The result of this study is that there is empirical evidence of the effect of the spillover effect of FDI on domestic firms in Savannakhet province.